Islamic Worldview in the Prevention of Radicalism of Islamic Religious Education Students at the University of Muhammadiyah Gresik - Noor Amirudin (Postgraduate Program Magister Pendidikan Agama Islam, 2023)
The background of this research is that today's students are not stable in presenting moderate Islamic thoughts that have become the basis of identity today, but must face a flood of information scrambling to influence their thinking and awareness in strengthening their extreme religious attitudes at a certain level can provoke horizontal conflict. As happened to students of Islamic religious education at the Muhammadiyah Gresik University recently, that among them there are those who take part in extra-campus activities such as the Student Da'wah Institute aimed at strengthening cultural-moral bonds, but in its current development their understanding has turned into an act of group struggle. and ideological. For this reason, an Islamic worldview is needed to provide control over their religious understanding which will be dynamic and tolerant in diversity. For this reason, a research method is needed to explore these problems using a qualitative approach, because qualitative research aims to capture meaning or understand certain symptoms, events, facts, events, realities or problems regarding social and human events with deep complexity. while the type of research that researchers use in this study is a case study. This study concludes that there is a need for the role of Islamic wordview which is carried out through andragogical PAI learning process activities on campus, in the context of teaching and learning activities in PAI study programs, the creativity of qualified professional lecturers in the field of Islam, including integrating actual themes designed to provide comprehensive insights fundamentals of Islam to PAI students so that they have a framework of Islamic thought that is solid and unswayed and more enthusiastic in exploring deeper Islamic scholarship, so as to be able to assess and filter various forms of deviation in Islamic religious teachings and to stem them from radicalism.